Kekuatan Pembuktian Surat Dibawah Tangan yang Dilegalisasi oleh Notaris (Studi Kasus Putusan Nomor 362/PID.B/2020/PN PDG) - Nanda, Novitra; Ismansyah, Ismansyah; Fendri, Azmi (UNES Law Review, 2023)
Humans as social beings are always in contact with other humans, where in human relations they often make agreements both verbally and in writing which lead to an agreement. An agreement made in writing intends to provide legal certainty and legal protection for both parties if a dispute occurs between them at any time. In a written agreement, the subject and object of the agreement will be clearly visible. While the object can be described as something that is done by the subject, namely things that are obligatory to the authorities against which party has the right. A written agreement can be made by private deed or by authentic deed. Authentic deed made by a Notary. Notary as a public official who is the only one authorized to make authentic deeds and other authorities determined by law. In court, if what is presented as evidence is only an underhanded deed considering the limited strength of evidence, then other supporting evidence is still being sought so that evidence is obtained which is considered sufficient to reach the truth according to law. Based on this, problems arise regarding: 1) What is the judge's consideration of Decision Number 362/Pid.B/2020/PN Pdg regarding private letters legalized by a Notary. 2) What are the legal consequences of private letters legalized by a Notary against Decision Number 362/Pid.B/2020/PN Pdg. This study uses the Normative method, namely by examining primary, secondary and tertiary legal materials. Based on the results of the research, the judge's consideration of Decision Number 362/Pid.B/2020/PN Pdg is related to private letters legalized by a Notary, proof of letters, namely the legalization of private deeds which only have formal evidentiary strength, namely the strength of evidence which provides certainty that an incident has actually occurred which is contained in the private deed by the parties and public officials have acknowledged it. single public prosecutor. The legal consequence of private documents legalized by a notary is that private deeds do not have perfect evidentiary legal consequences because they lie in the signatures of all parties to the agreement. An underhand deed only gives legal consequences of proof that are perfect for the benefit of the party to whom the signatory wants to provide evidence, while for third parties the legal consequences of proof are free.